A common wealth of learning : millennium development goals revisited - MacBeath, John E. C.; Younger, Mike, 1948- (Taylor and Francis, 2013)
A Common Wealth of Learning takes a look at the millennium development goals that were set out at the start of the century. Utilising a far reaching set of case studies from a large percentage of commonwealth countries, this book looks at what the colonial legacy has left us with; and what we can do to progress. Chapters discuss; Partnerships for Leadership and Learning Quality Education and the Millennium Development Goals Revisited: Reflections, Reality and Future Directions. Assessing the Impact of Education Sector Policy Refo.